Complete violin sonatas - Beethoven, Ludwig van. 1770-1827 (Dover Publications, 1990)
Beethoven´s ten violin sonatas, time-honored favorites of violinists, pianists and their audiences, reflect the great composer´s determination to make the interrelatioship between the violin and the piano a more intimate one, and to create a more even and intricate balance bertween the two instruments than had previously existed in the genre.